Frontispiece: Consecutive Single‐Crystal‐to‐Single‐Crystal Isomerization of Novel Octamolybdate Anions within a Microporous Hybrid Framework with Robust Water Sorption Properties - Ruiz‐Bilbao, Estibaliz; Iturrospe, Amaia; Reinoso, Santiago; Artetxe, Beñat; Beobide, Garikoitz; San Felices, Leire; Lezama, Luis; Gutiérrez‐Zorrilla, Juan M.; Darwish, Shaza; Sensharma, Debobroto; Zaworotko, Michael J. (Angewandte Chemie International Edition, 2023)
Polyoxometalates. The single‐crystal‐to‐single‐crystal isomerization of novel octamolybdate anions within a microporous hybrid framework with robust water sorption properties is reported by Beñat Artetxe in their Research Article (e202307436).